The Influence Of Corporate Governance Structure On Enterprise Risk Management Disclosure - Lestari, Sendang Ayu; Handayani, Susi; Mohd Ali, Mazurina (International Economic Conference of Business and Accounting, 2024)
This study aims to examine the effect of internal audit and risk management committee on Enterprise Risk Management Disclosure in financial sector companies listed on the Indonesian Stock Exchange for periode 2020 – 2022. The sample selection technique used was purposive sampling and obtained 96 financial sector companies so that total sample used was 288 samples. The data analysis method used is multiple regression analysis using SPSS 25 analysis software. Based on the result of the study, internal audit and risk management committee simultaneously and partially have significant effect on Enterprise Risk Management Disclosure.